COVID-19 Related to Liver Impairment and Its Impact on Chronic Liver Disease - Andri Sanityoso Sulaiman; Juferdy Kurniawan; Chyntia Olivia Maurine Jasirwan; Saut HH Nababan; Kemal F Calista; Cosmas Rinaldi A Lesmana; Irsan Hasan; Rino Alvani Gani; Baiq Kirana DN Mandasari (The Indonesian Society for Digestive Endoscopy, 2020)
By late December 2019, a novel beta-coronavirus, named as COVID-19 (2019-nCoV), was discovered in Wuhan, Hubei Province, China which epidemiologically linked to a Huanan seafood market in Wuhan. Coronavirus Disease 2019 or COVID-19 cases are growing rapidly from Wuhan to many countries, finding the health care system unprepared to face this threat. No effective drugs are clinically approved to manage the disease and strategies to protect the most vulnerable from developing severe illness and infection is still unclear. Information on how COVID-19 virus infection may affects many organs, especially the liver and the relevance of pre-existing liver disease in patients as a risk factor for the infection or disease severity are still scarce and inconclusive. Besides, the recommendation and consideration in liver transplant patients, hepatocellular carcinoma, or patient on immunosuppressive therapy still need further analysis Therefore, the information on the mechanism and treatment of COVID-19 related liver injury in patients with or without pre-existing liver disease should be considered.